ANALISIS FENOMENA ELEKTROHIDRODINAMIK MENGGUNAKAN PLASMA LUCUTAN KORONA DC POSITIF DENGAN KONFIGURASI ELEKTRODA MATA PAHAT DAN TITIK TENGAH-BIDANG PADA MINYAK KELAPA SAWIT - Charis Munajib; Asep Yoyo Wardaya; Zaenul Muhlisin; Isnain Gunadi (BERKALA FISIKA, 2022)
Research has been carried out on the analysis of I-V characteristic curves and electrohydrodynamic phenomena using palm oil with a positive DC corona discharge generator with Chisel Eye and Mid-Field electrode configurations. This study aimed to obtain the effect of several variations used on the characteristic curve and distribution of ion winds on electrohydrodynamic phenomena. This research was conducted with 6 variations of the size of the dimensions of active electrodes and variations in the distance between the electrodes (c) 0.5 cm, 1 cm, 1.5 cm, and 2 cm. In the study of the I-V characteristic curve, the results show that with the increase in the applied voltage, the stronger the current produced will increase. At electrode D and a distance of 0.5 cm, the circuit is given a voltage of 5.32 kV produces a current of 10.5 A, whereas if the circuit is given a voltage of 6.34 kV it produces a current of 27.5 A. In the study of the analysis of electrohydrodynamic phenomena, it was found that if the variation used changed it would affect the diameter of the deformation of the palm oil in the form of a circle. At electrode D, at a distance of 0.5 cm with a voltage of 7.14 kV it produces a circular oil deformation diameter of 2.7 cm, while at a distance of 1 cm with a voltage of 11.23 kV produces a circular oil deformation diameter of 5.5 cm.